Fragments of Sources Relating to the Grand Tour of the Counts of Clary-Aldringen from 1727 (Theatrum historiae, 2006)
The paper is a contribution to the history of noble travelling and its change in the first half of 18th century. Recent literature has come to the conclusion that deep changes in grand tour (Kavalierstour) of young nobles passed in 1720s and 1730s. Much more attention was newly devoted to the time consuming specialized education and the attraction of the European courts decreased. This hypothesis was compared with the travelling of young noble brothers Franz Wenzel and Johann Anton of Clary-Aldringen. Their journey started in 1727 and it could be reconstructed thanks to several pieces of their diary. The Clary-Aldringens belonged to the wealthy Czech noble families whose ancestors had come to Bohemia as successful soldiers during the Thirty Years´ War. They created a large dominion mainly in northern Bohemia with the centre in well known spa Teplice. The rise of the family reached its peak in 1767 when Franz Wenzel got a statute of prince (Fürst). His and his brother´s grand tour led to the western Europe at the end of 1720s. The fragments of their diary show that they travelled with their hofmeister and one servant from Prague via Nuremberg, Erlangen, Bamberg and Würzburg to the Netherlands. Their stay had two basic aims. They visited the court of the governor of the Austrian Netherlands in Brussels and then they studied at the famous university in Leiden in the United Provinces. They devoted their time to the course of Jus publicum by the well known teacher Johann Jakob Vitriarius. They also made some trips through the Netherlands and they observed the most important towns and ports (Amsterdam, the Hague, Rotterdam, Utrecht, etc.). Finally, the paper comes to the conclusion that this journey reminds much more the old style of grand tours. The Clary-Aldringens studied in Leiden indeed but their course was short (approximately 2 months only) and the fragments of their diary speak rather about the court stays and visits of different monuments. That means that they did not study to obtain the academic degrees. The paper includes also an edition of the fragments of the diary.